Role of Salbutamol in the Management of Transient Tachypnea of the New Born - Ullah, Hayat; Amir, Sabahat (Indus Journal of Bioscience Research, 2025)
Background: Transient tachypnea of the newborn (TTN) is a common respiratory disorder in the early neonatal period due to delayed clearance of fetal lung fluid. Salbutamol, a β2-adrenergic agonist, may enhance lung fluid clearance through stimulation of epithelial sodium channels and Na-K-ATPase. However, the therapeutic role of Salbutamol in TTN management remains controversial with limited clinical evidence, necessitating further investigation. Objective: To compare the mean change in transient tachypnea of newborn score with inhaled salbutamol and normal saline. Study Design: It was a randomized Controlled Trial. This study has been registered with the ClinicalTrials.gov database under the registration number NCT06921291. Duration and Place of Study: This study was conducted between August 2024 and December 2024 in the pediatric department of Khyber Teaching Hospital in Peshawar. Methodology: A total of 60 neonates with TTN were randomized into two groups (30 in each group) using blocked randomization. Eligible participants included neonates with gestational age >36 weeks of both genders presenting with TTN. Group A received a single nebulized dose of salbutamol (0.15 mg/kg) in 0.9% saline, while Group B received nebulized 0.9% saline. Both groups also received oxygen and IV fluids. Results: The mean gestational age at birth was 39.3 ± 1.32 weeks in Group A and 38.93 ± 1.23 weeks in Group B. Males comprised 46.7% in Group A and 66.7% in Group B, while females accounted for 53.3% and 33.3%. Group A demonstrated a significantly greater mean reduction in TTN scores (5.61 ± 1.22) compared to Group B (0.97 ± 0.73, p = 0.000). Conclusion: Inhaled salbutamol significantly improves TTN scores compared to normal saline, demonstrating consistent efficacy.